Comparative time-course transcriptome analysis of two contrasting alfalfa (Medicago sativa L.) genotypes reveals tolerance mechanisms to salt stress - Ma, Dongmei; Cai, Jinjun; Ma, Qiaoli; Wang, Wenjing; Zhao, Lijuan; Li, Jiawen; Su, Lina (Frontiers in Plant Science, 2022)
Salt stress is a major abiotic stress affecting plant growth and crop yield. For the successful cultivation of alfalfa (Medicago sativa L.), a key legume forage, in saline-affected areas, it’s essential to explore genetic modifications to improve salt-tolerance. In order to investigate the molecular mechanism in alfalfa under salt stress conditions, we conducted transcriptome assay of two comparative alfalfa genotypes, Adina and Zhaodong, following a 4 h and 8 h’s 300 mM NaCl treatment. From the sequenced libraries we obtained 875,023,571 transcripts and 662,765,594 unigenes, and 520,091 assembled unigenes were annotated in at least one database. Among them, we identified 1,636 differentially expression genes (DEGs) in Adina, of which 1,426 were up-regulated and 210 down-regulated, and 1,295 DEGs in Zhaodong, of which 565 were up-regulated and 730 down-regulated. GO annotations and KEGG pathway enrichments of the DEGs based on RNA-seq data showed that DEGs were involved in (1) ion and membrane homeostasis, including ABC transporter, CLC, NCX, and NHX; (2) Ca2+ sensing and transduction, including BK channel, EF-hand domain, and calmodulin binding protein; (3) phytohormone signaling and regulation, including TPR, FBP, LRR, and PP2C; (4) transcription factors, including zinc finger proteins, YABBY, and SBP-box; (5) antioxidation process, including GST, PYROX, and ALDH; (6) post-translational modification, including UCH, ubiquitin family, GT, MT and SOT. The functional roles of DEGs could explain the variations in salt tolerance performance observed between the two alfalfa genotypes Adina and Zhaodong. Our study widens the understanding of the sophisticated molecular response and tolerance mechanism to salt stress, providing novel insights on candidate genes and pathways for genetic modification involved in salt stress adaptation in alfalfa.